Experimental Glass Ionomer Cement Containing Gallic acid: Antibacterial Effect and Fluoride Release an in vitro Study - Elsharkawy, Saher M.; Gomaa, Yasser F.; Gamal, Reem (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract: Aim: Assessment of antibacterial effect and fluoride release on glass ionomer cement (GIC) modified by different concentrations of gallic acid (GA) and their effect on working and setting time. Methodology: Four groups were tested, group I (control non modified group) and groups II-IV represent GIC modified by GA in three different concentrations (125mg/ml, 62.5mg/ml and 31.25mg/ml GA powder / GIC liquid respectively). Antibacterial effect against Streptococcus Mutans (S. Mutans) was determined after 24hr by broth dilution method. Fluoride release was evaluated after three time intervals 24, 48 and 96hr using spectrophotometer. Working and setting time were measured in all groups by indentation method. Results: Increasing the concentration of GA significantly increase the antibacterial effect. For all time intervals, the highest fluoride release were observed in group IV and the lowest were in group I. After 24hr groups II, III and IV were significant to group I, while after 48 and 96hr group IV was significant to group I. In addition, working and setting time significantly increased with increasing the GA concentration. Conclusion: Gallic acid improve the antibacterial effect of GIC against S. Mutans and also improve the fluoride release. The increase in working and setting time of GA modified groups were still within the limit given by ISO 9917–1:2007 specifications.